PENGARUH KEMAMPUAN MANAJEMEN, MOTIVASI FRANCHISE, BRAND IMAGE DAN PROMOTION STRATEGY TERHADAP KEBERHASILAN USAHA FRANCHISE (Studi Kasus : Primagama Indonesia Timur) - Yunita Primasanti; Imam Djati Widodo (Teknoin, 2017)
Enterprises that can be directly executed properly without having to market from the beginning is to buy products or services that have become, namely Franchise. It is the licensing of an overall business format in which the franchisor grants a license to a number of dealers or franchisee to market a product / service and conduct a business developed by franschisor using a name brand, Trademarks, specialist merchandising services and how to do business that the franchisor owns. This data analysis technique is by using quantitative technique with path analysis. Variable there are 6, which consists of Management Ability, Motivation Franchise, Brand Image and Promotion Strategy. These variables are called independent variables. Performance Franchise enter the dependent variable, while Franchise Cooperation entered variable factor. The sample in this research is 120 respondents, with data collection technique through questionnaire with likert scale. The result of this research is that the variable of Management Capability, Franchise Motivation, Brand Image and Promotion Strategy have direct influence to Franchise Cooperation, but have no direct effect on Knelan Franchise.